Pengaruh Kinerja Keuangan terhadap Harga Saham Perbankan BUMN - Tola, Brenda Fitria; Budi Artani, Ketut Tri; Putra Adnyana, I Wayan Diana (Universitas Muhammadiyah Metro, 2024)
This research aims to determine the effect of financial performance on the stock prices of state-owned banks in the Indonesia Stock Exchange. The data analysis method used in this study includes classical assumption tests, multiple linear regression analysis and hypothesis testing. According to the partial test findings or T test, ROE, PBV and EPS have an impact on stock prices, whereas PER, NPL, CAR, and Dividend Yield have no such impact. The factors ROE, PBV, PER, EPS, NPL, CAR and Dividend Yield affect stock prices simultaneously or in the F test. Furthermore, the researcher conveys several suggestions, namely, for investors or prospective investors, that when making a decision to invest, you should consider the financial performance contained in the company's financial reports to estimate share price movements. Furthermore, the company must always be able to improve its financial performance so that it can increase profits for the company and attract investors to invest in shares. For future researchers, they can expand the research by extending the research period by adding more years of observation and increasing the research sample